Searching for A Better Educational System: Language Planning in Competency-Based School Curriculum - Rushiti, Rozana; Kananaj, Anila (RGSA : Revista de Gestão Social e Ambiental, 2024)
Purpose: The new European school curriculum focuses on innovation, competency-based learning and the integration of technology as ways to increase the quality of education and better prepare students for the challenges of the 21st century. This study investigates the effects of implementation of this curriculum, highlighting its benefits and potential challenges, especially in relation to the standard language.